2015
DOI: 10.1108/jmtm-02-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

E-maintenance research: a multifaceted perspective

Abstract: Purpose -The purpose of this paper is to develop a multifaceted perspective on e-maintenance research and practice over 12 years from 2002 to 2013. Design/methodology/approach -A qualitative research approach is conducted through analysing e-maintenance literature published in peer-review journals from 2002 to 2013 in operations management, information systems, computer science and engineering disciplines. Findings -A multifaceted perspective that reflects evolutionary, managerial, and technological domains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…During the study, the outcomes of implementing eMaintenance were also identified, i.e., improved information on condition, increased capacity, more efficient maintenance, and optimized costs, which in previous literature only has been studied in isolation and not aggregated [1,23,31]. This qualitative study has produced the same results as previous research on the possibilities; however, in addition, increased sustainability was identified as a main driver for eMaintenance.…”
Section: Theoretical Contributionsmentioning
confidence: 71%
See 2 more Smart Citations
“…During the study, the outcomes of implementing eMaintenance were also identified, i.e., improved information on condition, increased capacity, more efficient maintenance, and optimized costs, which in previous literature only has been studied in isolation and not aggregated [1,23,31]. This qualitative study has produced the same results as previous research on the possibilities; however, in addition, increased sustainability was identified as a main driver for eMaintenance.…”
Section: Theoretical Contributionsmentioning
confidence: 71%
“…The report concludes by describing limitations and recommendations for future research. There are countless opportunities when it comes to eMaintenance, which have also been discussed in the literature [10,11,20,23]. In this report, we have therefore designed a framework for which capabilities are crucial when an organization wants to implement eMaintenance; we also identified the outcomes that arise when the transition to eMaintenance has been carried out.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such integration will contribute to the achievement of primary objectives of active maintenance such as recording functioning quality statistics and using monitoring techniques (e.g. vibration measurement, thermography or ferrography), improve the effectiveness and efficiency of the maintenance process, reduce associated risks, and contribute to business sustainability [33]. Computerization is essential to a successful framework development endeavor.…”
Section: Emergingmentioning
confidence: 99%
“…[12] Remote and realtime assessment of machine's performance requires an integration of many different technologies including sensory devices, reasoning agents, wireless communication, virtual integration and interface platforms. [2] Fig. 1.…”
Section: Intelligent Maintenance Systems and E-businessmentioning
confidence: 99%